12.58=-8(8m+5)-3(-m+8)

Simple and best practice solution for 12.58=-8(8m+5)-3(-m+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12.58=-8(8m+5)-3(-m+8) equation:


Simplifying
12.58 = -8(8m + 5) + -3(-1m + 8)

Reorder the terms:
12.58 = -8(5 + 8m) + -3(-1m + 8)
12.58 = (5 * -8 + 8m * -8) + -3(-1m + 8)
12.58 = (-40 + -64m) + -3(-1m + 8)

Reorder the terms:
12.58 = -40 + -64m + -3(8 + -1m)
12.58 = -40 + -64m + (8 * -3 + -1m * -3)
12.58 = -40 + -64m + (-24 + 3m)

Reorder the terms:
12.58 = -40 + -24 + -64m + 3m

Combine like terms: -40 + -24 = -64
12.58 = -64 + -64m + 3m

Combine like terms: -64m + 3m = -61m
12.58 = -64 + -61m

Solving
12.58 = -64 + -61m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '61m' to each side of the equation.
12.58 + 61m = -64 + -61m + 61m

Combine like terms: -61m + 61m = 0
12.58 + 61m = -64 + 0
12.58 + 61m = -64

Add '-12.58' to each side of the equation.
12.58 + -12.58 + 61m = -64 + -12.58

Combine like terms: 12.58 + -12.58 = 0.00
0.00 + 61m = -64 + -12.58
61m = -64 + -12.58

Combine like terms: -64 + -12.58 = -76.58
61m = -76.58

Divide each side by '61'.
m = -1.255409836

Simplifying
m = -1.255409836

See similar equations:

| 6x+1+5=4x-2 | | y=5(x+3)-20 | | x^3-30x^2+400=0 | | 4p+3p=0 | | 3/4x3/1 | | y=3(x+3) | | 54-9x=12+12x | | 3/4(3x) | | x-5y-2=21 | | (x-(3+i))(x-(3+i))=0 | | 0.666(x+4)=0.375(x-3) | | 2/1,2=5/k | | 3(x-.1)=15 | | (x^3+1)(x+1)+2ax^2=0 | | 4(x^2-5)=12 | | 0.70x+0.50(70)=0.35(136) | | 2x^2-50=x^2-1 | | 3(3x+2)=3x+18 | | 4-3x=-x^2+3x | | -6-2(7x-2)=4(-6x+2)-4 | | 8(2x-9)+1=16x | | 0.7m-6.7-5.2m=-5.9-4.5m-0.8 | | 7x^2+8x=x^2 | | 6Z+2=0 | | 4x+7x-54=72-7x | | (x^3+1)(x+1)=0 | | (x-(3+i))=0 | | 18(x+4)-2=2(x+5)-3x | | y^2=4y+96 | | 4(x-5)-8=17 | | (x-(3+1))(x+(3-i))=0 | | -2-(3x-8)=4(-8x-7)+5 |

Equations solver categories